Fixing the game : how runaway expectations broke the economy, and how to get back to reality - Martin, Roger L. (Boston, Mass. : Harvard Business School Pub., 2011)
Using the National Football League as his primary example, Martin illustrates that it is possible to take a much more thoughtful and effective approach than we now do to the intersection of the real and the expectations markets and to governance in general in the capital markets. Martin shows how we can act to end the destructive cycle of increasing volatility, decreasing investor returns, and ongoing bad behavior by executives.
Fixing a broken game -- Maximizing customer delight -- Restoring executive authenticity -- Repairing governance -- The insanity of 2&20 -- A bold vision for companies & executives.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Corporations -- United States; Industrial management -- United States; Corporate governance -- United States; Capitalism -- United States; Financial crises -- United States; Capitalism; Corporate governance; Corporations; Financial crises; Industrial management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; United States; elektronické knihy; electronic books